2008
DOI: 10.5326/0440116
|View full text |Cite
|
Sign up to set email alerts
|

Palliation of Clinical Signs in 48 Dogs With Nasal Carcinomas Treated With Coarse-fraction Radiation Therapy

Abstract: Data from 48 dogs with nasal carcinomas treated with palliative radiation therapy (PRT) were retrospectively reviewed. Factors potentially influencing resolution of clinical signs and survival after PRT were evaluated. Clinical signs completely resolved in 66% of dogs for a median of 120 days. The overall median survival time was 146 days. Duration of response to PRT was shorter in dogs that had clinical signs for <90 days before PRT. Survival times were shorter in dogs that had partial or no resolution of cli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

7
53
3
5

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(68 citation statements)
references
References 26 publications
7
53
3
5
Order By: Relevance
“…The median survival time in their study was 212 days. Gieger et al [7] reported data from 48 dogs with nasal carcinomas treated with hypofractionated radiation therapy due to the extent of local disease or concurrent disease (40%) and the owners requesting palliative radiotherapy because of concerns about cost, potential for toxicity or travel/hospitalization associated with definitive radiation therapy. The total radiation dose ranged from 16 to 40 Gy (median 24 Gy), and the dose per fraction ranged from 4 to 10 Gy (median 8 Gy).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The median survival time in their study was 212 days. Gieger et al [7] reported data from 48 dogs with nasal carcinomas treated with hypofractionated radiation therapy due to the extent of local disease or concurrent disease (40%) and the owners requesting palliative radiotherapy because of concerns about cost, potential for toxicity or travel/hospitalization associated with definitive radiation therapy. The total radiation dose ranged from 16 to 40 Gy (median 24 Gy), and the dose per fraction ranged from 4 to 10 Gy (median 8 Gy).…”
Section: Discussionmentioning
confidence: 99%
“…The reported prognostic factors are destruction of the cribriform plate [1], tumor type [1,27], tumor stage [1,3,4,9,11,27], age >10 years [11], regional lymph node or pulmonary metastasis [8], resolution of clinical signs after treatment [7,23], tumor regression [28], facial deformity [23], three or more treatments/week [30] and a cumulative minimum tumor dose of at least 37 Gy [30]. In regard to the stage in particular, various stage classifications have been reported, and lower stages resulted in longer survival than higher stages [1,3,4,9,11,27].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations